Erectile Function and Sexual Activity Are Declining in the Younger Generation: Results from a National Survey in Japan - Akira Tsujimura; Shinichiro Fukuhara; Koji Chiba; Tsuyoshi Yoshizawa; Hikaru Tomoe; Masato Shirai; Kazunori Kimura; Eiji Kikuchi; Eri Maeda; Yoshikazu Sato; Atsushi Nagai; Koichi Nagao; et al. (The World Journal of Men's Health, 2025)
Purpose: Twenty five years have passed since the first national survey on erectile dysfunction (ED) in Japan. The Japanese Society for Sexual Medicine conducted a nationwide survey on the actual status of sexual function targeting men over 20 years old in Japan using validated questionnaires commonly used in clinical practice. Materials and Methods: Japanese men aged 20 to 79 years participated in our online epidemiological study on sexual dysfunction. Erectile status was assessed by direct questioning and specific questionnaires. Risk factors and frequencies of sexual intercourse, masturbation, nocturnal erections, and feeling sexual desire were assessed. The prevalence of these risk factors was compared between men with and without ED. Prevalence and frequencies were calculated for each 5-year age group. Main outcomes were the prevalence and number of patients with ED and simultaneous evaluation of age-related variations. Results: Direct questioning of the men revealed that 13.0% felt troubled by ED. Although 81.0% of them had at least some ED symptoms based on a Sexual Health Inventory For Men score of ≤21, the prevalence of men with ED by Erection Hardness Score (EHS), the most appropriate questionnaire for Japanese with low sexual activity, was 30.9%, indicating that 14,012,596 men have ED. Most risk factors were related with ED, whereas frequencies of sexual intercourse, masturbation, nocturnal erections, and feeling sexual desire were affected by aging. However, the low frequency of these factors in the young generation was surprising. Conclusions: The EHS-based assessment revealed a prevalence of ED of 30.9%, which affected approximately 14 million men, and that the sexual desire, erection stiffness, orgasms, and satisfaction were lower than expected in young Japanese men, especially those aged 20 to 24 years, although those factors tended to worsen with aging. We believe that these findings actually reveal the current sexual status of men in Japan.